Efektifitas Konten Edukasi Keislaman di Platform Media Sosial: Analisis Resepsi Khalayak Generasi Z - Noratur Rahmah; Sayyid Afif; Muhammad Saleh; Nurkhofifah Nurkhofifah; Neiva Zaida Hasanah Saragih; Haidar Sidqan Alkhalid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to evaluate the effectiveness of Islamic educational content on social media platforms and how Generation Z receives the content. The problem raised is the low understanding and interest of Generation Z in Islamic values, even though they are active in using social media. The research method applied is a qualitative approach using interviews and surveys involving 150 respondents from Generation Z. The results of the study indicate that Islamic educational content presented in an interesting and interactive way can have a positive impact on the understanding and interest of Generation Z. Respondents stated that attractive visual elements, the use of simple language, and the relevance of the content to everyday life increased their interest in the material. However, there are still challenges in creating consistent and high-quality content. Based on these findings, it is recommended that further research dig deeper into the strategy for developing more innovative Islamic educational content that is in accordance with changes in the behavior of social media users, and conduct longitudinal research to monitor changes in attitudes and understanding of Generation Z over time. This study is expected to contribute to the development of da'wah through social media with a more effective and attractive approach for the younger generation.